Geo-blocking: A literature review and new evidence in online audio-visual services - Annette Broocks; Néstor Duch-Brown; Estrella Gómez-Herrera; Bertin Martens (European Commission, Joint Research Centre (JRC), 2020)
This paper is composed of two different parts. In the first part we provide a review of the existing literature dealing with geo-blocking in copyright-protected content. The material is divided between studies that focus on non-audio-visual content and those dealing wit h audiovisual content. In the second part, we offer recent evidence of cross-border availability of audiovisual content in VoD platforms in the EU.
Keywords: 330; geo-blocking; copyright